PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP DISIPLIN KERJA KARYAWAN PT. SHELTER NUSANTARA - Dwiki Hisyamul Mubarok; Sulastri Irbayuni (Universitas Islam Kadiri, 2021)
This study aims to determine the effect of leadership and compensation on the work discipline of employees of PT. Shelter Nusantara. The population of this study were employees of PT. Shelter Nusantara, which amounts to 119. The sampling technique in this study used a simple random sampling technique using the Slovin formula, from the results of the calculation of the slovin formula, a sample of 54 respondents was obtained. The analytical technique used in this study is to use the Partial Least Square (PLS) application. According to the results of the study, it was found that: 1) Leadership has a contribution to work discipline, which means that the better the leadership in a company, the better the work discipline in the company. 2) Compensation has a contribution to work discipline, which means that the better the compensation, the better the work discipline. The company needs to improve the existing leadership and the compensation given to employees so that employee work discipline increases.